Orthogonal Analysis of Axial Bearing Capacity of Short Columns Reinforced by Circular Steel Tube and Ultra High Performance Concrete with Coarse Aggregate - TANG Jiajun; WANG Tan; LI Jiuyang (Renmin Zhujiang)
This paper analyzes the influence of outer diameter of steel tube, wall thickness of steel tube, steel strength and concrete strength on the axial bearing capacity of short columns reinforced by circular steel tube and ultra high performance concrete with coarse aggregate (UHPC-CA) by orthogonal test. The results show that: The influence of various factors on the axial bearing capacity of short columns reinforced by circular steel tube and UHPC-CA is in the order of steel tube outer diameter > steel strength > steel tube wall thickness > concrete strength. The axial bearing capacity increases with the increase of outer diameter, wall thickness and strength of the steel tube, decreases slightly first and then increases gradually with the increase of UHPC-CA strength, and increases with the increase of hoop coefficient. With the increase of the diameter-thickness ratio, the axial bearing capacity of Q235 steel short columns decreases, while that of Q345 and Q390 steel short columns increases.